PENGARUH PENAMBAHAN KITOSAN TERHADAP KARAKTERISTIK KERUPUK GENDAR - Beti Cahyaning Astuti (LPPM Universitas Terbuka, 2017)
Rice cracker is a local crispy snack made of cooked rice as the main component and traditionally bleng as an additive that function as a thickening agent. However, bleng contains borax, an element which is harmful for human health. This research was important to substitute the role of bleng as a thickening agent. The objective of this research were to evaluate the effect of chitosan addition on physical, chemical, and organoleptic characteristics of fried rice cracker. Based on thephysical analysis ofunfolding rice cracker was 28,970-45,487% and oil adsorption was24,406-40,925%. Based on the chemical analysis of the content of waterrice cracker 1,275-1,986%; ash content of 0,311-1,775%; fat 31,511-33,508%; proteins 4,185-6,250%; carbohydrates 58,546-59,744%. Organoleptic test to color and taste of the fried rice cracker gave the significant results on all treatments. Kerupuk gendar merupakan produk makanan ringan yang terbuat dari bahan dasar beras dengan bahan tambahan bleng yang berfungsi sebagai agen pengenyal. Namun, bleng mengandung boraks, unsur yang berbahaya bagi kesehatan manusia. Penelitian ini bertujuan untuk mengevaluasi pengaruh penambahan kitosan sebagai pengganti bleng pada karakteristik fisik, kimia, dan organoleptik kerupuk gendar. Berdasarkan analisis fisik kerupuk gendar goreng diketahui daya kembang sebesar 28,970-45,487% dan daya serap minyak sebesar 24,406-40,925%. Berdasarkan analisis kimia kerupuk gendar goreng diketahui kadar air 1,275- 1,986%; kadar abu 0,311-1,775%; lemak 31,511-33,508%; protein 4,185-6,250%; dan karbohidrat 58,546-59,744%. Hasil analisis sensori kerupuk gendar goreng berpengaruh nyata terhadap warna dan rasa.